Regulation of Cx43 and its role in trichloroethylene-induced cardiac toxicity in H9C2 rat cardiomyocytes. (May 2023) - Teng, Zhongkun; Jiang, Bin; Wang, Jianming; Liu, Tiantian; Aniagu, Stanley; Zhu, Ziyu; Chen, Tao; Jiang, Yan
Abstract: Trichloroethylene (TCE), a widespread environmental contaminant, has been linked to congenital heart defects. Abnormal regulation of Connexin 43 is closely associated with various cardiac diseases. However, it is yet to be established how Cx43 responds to environmental pollutants. Here, we aim to explore the role of Cx43 in TCE-induced cardiac toxicity using H9C2 cardiomyocytes. EdU incorporation assay and cell cycle analysis revealed that increased number of TCE-treated cells entered into the S stage, indicating that TCE exposure provoked cell proliferation. Additionally, compromised mitochondrial function was observed in TCE-treated cells, and inhibition of mitochondrial permeability transition pore (mPTP) with Cyclosporin A or eliminating mitochondrial ROS by MitoQ alleviated the TCE-induced cardiac toxicity. Importantly, TCE exposure increased the protein expression levels of Cx43 and stimulated the recruitment of Cx43 to the mitochondria. TCE exposure disrupted canonical Wnt signal pathway, resulting in downregulation of antioxidant genes and β-catenin. The adverse effects of TCE on Wnt signal pathway activation, mitochondrial function and cell proliferation were efficiently counteracted by either Cx43 knockdown or pharmaceutical activator of Wnt signaling, CHIR-99021. Taken together, our results for the first time revealed that dysregulation of Cx43 mediates TCE-induced heart defects via mitochondrial dysfunction and Wnt signaling inhibition, suggesting that Cx43 can be a potential molecular marker or therapeutic target for cardiac diseases caused by environmental pollutants. Graphical abstract: Image 1 Highlights: TCE provokes cardiac cell abnormal proliferation and mitochondrial dysfunction. TCE exposure leads to Cx43 upregulation and translocation to the mitochondrion. Cx43 mediates ROS production and downregulation of Wnt signaling upon TCE exposure. Wnt signaling is involved in TCE-induced cardiac abnormal proliferation and mitochondrial dysfunction.